Modeling and Tolerance Analysis of Compliant Mechanism for Axis-Symmetric Mass Comparator - Yoon, Kyung Taek; Choi, Young Man (IEEE/ASME Transactions on Mechatronics, 2024)
In this study, modeling and analysis of the compliant mechanism of an axis-symmetric mass comparator are performed to deeply understand the static and dynamic characteristics for the measurement performance improvement. Herein, the model is established using a multibody matrix method, which interprets the mechanism as a multibody mass-spring model in a matrix form. As all dimensions are parametrized in the matrix method, analysis can be performed effortlessly without formalization. Furthermore, through combination with optimization, the method can determine a force equilibrium state of the mass comparator, which is a multiple input-multiple output system, under various conditions. Static stiffness and dynamic mode are analyzed based on flexure parameter for concurrently maximizing mechanical sensitivity and securing dynamic stability. In addition, measurement uncertainty in the ground-tilt and eccentric loading conditions is predicted and compared with the experimental results. Finally, parametric tolerance analysis and Monte-Carlo simulation are performed to examine how the tolerances affect the measurement uncertainty.
Keywords: Electromagnetic force compensation; Electromagnetic force compensations; Forces measurements; Manufacturing process; Mass comparator; Matrix methods; Multi-body; Sensitivity; Symmetrics; Tolerance analysis; Compliant mechanism; electromagnetic force compensation (EMFC); mass comparator; tolerance analysis